Why is Mexico highly vulnerable to climate change? - Rodríguez Moreno, Victor Manuel; Medina García, Guillermo; Diaz Padilla, Gabriel; Ruiz Corral, Jose Ariel; Estrada Avalos, Juan; Mauricio Ruvalcaba, Jorge Ernesto (Revista Mexicana de Ciencias Agrícolas, 2021)
This manuscript provides an overview of the vulnerability of Mexico, as a geographic region, to the impacts of climate change. It is in the dynamism of the primary sector where global climate changes have the greatest influence. To rescale global observations at a local, regional and national scale, INIFAP as a public research center, provides technological solutions available to users, decision makers, researchers, academics and consultants. Since its creation, the institute maintains lines of research to study the impacts of climate change on agriculture, livestock and forestry. This is carried out through the organization of national and international technical-scientific exchange meetings and the execution of research and service projects. Through the integration and analysis of databases, the implementation of machine learning techniques in computing architectures, time series of satellite images and data on exchange processes between the ground cover and the atmosphere, the National Laboratory Modeling and Remote Sensors offers the user products and services based on ICTs. Numerical rain and drought forecasts make up the institutional offer to provide useful information to mitigate the effects of climate change in the primary sector. Through these products and services, a paradigm shift is promoted for the study of the impacts of climate change in Mexico.